Socioeconomic inequalities in knee pain, knee osteoarthritis, and health-related quality of life: a population-based cohort study in southern Sweden. (4th March 2017) - Kiadaliri, AA; Gerhardsson de Verdier, M; Turkiewicz, A; Lohmander, LS; Englund, M
Abstract : Objectives : To determine socioeconomic inequalities in frequent knee pain (FKP), knee osteoarthritis (OA), and associated health-related quality of life (HRQoL) in Sweden. Method : In 2007 a postal questionnaire about knee pain was sent to a random sample of 10 000 residents of Malmö, Sweden (7402 individuals responded). Subjects reporting pain with duration ≥ 4 weeks in one or both knees in the past 12 months were classified as having FKP. A random sample of 1527 subjects with and without FKP attended a clinical and radiographic knee examination and responded to generic and disease-specific HRQoL questionnaires. We used the individuals' level of education and occupation as socioeconomic status (SES) measures, and we calculated the relative index of inequality (RII) using Poisson regression with robust standard errors adjusted for age and gender. We applied weighting to account for a possible selection bias that might arise from non-responses in the study. Results : With education, the RIIs for FKP and knee OA were 0.71 [95% confidence interval (CI) 0.61–0.84] and 0.56 (95% CI 0.34–0.93), respectively. With occupation, the corresponding figures were 0.70 (95% CI 0.60–0.82) and 0.59 (95% CI 0.37–0.94), respectively. There were socioeconomic gradients in HRQoL in favour of people with better SES. RIIs for FKP and HRQoL but not knee OA were essentially similar after additional adjustment for mediators. Conclusions : In Sweden there are socioeconomic gradients related to both FKP and knee OA as well as HRQoL in favour of people with better SES. SES should be taken into account in health resource allocation pertaining to knee-related disorders.